KEABSAHAN KONTRAK KERJA FREELANCE DENGAN MEDIA DIGITAL DI AMAZONE PONTIANAK DALAM PANDANGAN HUKUM ISLAM KONTEMPORER - Muhammad Arif Ikhsan (Fakultas Syariah (Syari'ah Faculty ), 2018)
Freelance work contract with digital media is a contracting activity that follows the development of contemporary era in the business world. Basically, Amazone Pontianak responds to the development of this era by performing work contracts to freelancers by utilizing internet and computer technology. Companies certainly get a positive impact by doing this contract because for every company as long as the new thing is effective and efficient then everything needs to be done including the practice of freelance work contract with this digital media. The way contract work is made with digital media is not the same as a general contract work without using technology. Important points in the practice of employment contracts at Amazon Pontianak with digital media are: 1) Contract agreement items. 2) Approval of freelance contract. 3) Inspection of contract beneficiary data. Freelance work contract with digital media made by Amazone Ahmad Yani Mega Mall Pontianak fall into the category of lease (ijarah) in the concept of Islamic law because the pillars and terms in freelance work contract with digital media is in accordance with harmonies and terms on ijarah.